Gynecologic Surgery during the COVID-19 Pandemic: Is Universal Screening Mandatory? - Wilasinee Areeruk; Keerati Chiengthong; Somsook Santibenchakul; Shina Oranratanaphan; Tarinee Manchana (Hindawi Limited, 2021)
This study is aimed at evaluating the results of the universal preoperative screening for COVID-19 in gynecologic cases operated on during its outbreak in a tertiary care hospital in Bangkok, Thailand. A retrospective descriptive study was done on all patients who underwent elective or emergency gynecologic surgeries during the pandemic period in Thailand (April 15 to June 5, 2020). The COVID-19 screening results by symptom-based screening, risk-based screening, and RT-PCR for COVID-19 were collected from the electronic medical records. Among 129 patients who underwent gynecologic surgeries, none had a positive RT-PCR for COVID-19. Symptom-based screening found no patients with positive symptoms for COVID-19. Risk-based screening found 4 patients (3.1%) who were in contact with suspected or confirmed COVID-19 cases and 4 patients (3.1%) who were healthcare personnel. In conclusion, routine preoperative RT-PCR for COVID-19 may need to be reconsidered among asymptomatic individuals in a low-prevalence country during the well-controlled COVID-19 situation. Larger studies are required to ascertain the benefit of universal preoperative COVID-19 testing.